Analytical Review: Methods of Determination for Ledipasvir and Velpatasvir in Pharmaceutical and Biological samples - Sebaiy, Mahmoud M. (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
Infection due to hepatitis C virus (HCV) is a leading cause for severe chronic liver disease, which can result in progressive liver damage such as cirrhosis and hepatocellular carcinoma. Thus, it is considered to be a great worldwide health problem specifically in Egypt, which has the greatest prevalence of the epidemic problem of HCV in the world in accordance with the reported Egyptian Demographic Health Survey that had reached 14.7%. Hence, prevention of HCV becomes a national priority. Various techniques were used for the analysis of LDS in pure forms, in their pharmaceutical formulations and in biological fluids. This literature review represents an up-to-date survey about all reported methods that have been developed for the determination of LDS and VLP in their pure form, combined form with other drugs, combined form with degradation products, and in biological samples such as liquid chromatography, spectrophotometry, spectrofluorimetry, and electrochemistry.